Invasive pneumococcal and Haemophilus influenzae type b disease in the Autonomous Province of Vojvodina, Serbia (2003–2024): trends, vaccination impact, and serotype dynamics - Ristić, Mioljub; Petrović, Vladimir (Vojnosanitetski pregled, 2026)
Background/Aim. Invasive pneumococcal disease (IPD) and invasive Haemophilus influenzae type b (Hib) disease remain associated with significant morbidity and mortality. The aim of the study was to analyze long-term trends, age-specific and seasonal disease patterns, clinical outcomes, IPD serotype distribution, and the impact of immunization programs on these diseases in the Autonomous Province (AP) of Vojvodina, Serbia, from 2003 to 2024. Methods. A descriptive population-based study was conducted using data from the regional communicable disease surveillance system coordinated by the Institute of Public Health of Vojvodina. All reported cases of IPD and invasive Hib disease were included in the analysis. Results. The Hib immunization program introduced in 2006 led to a sustained reduction in invasive Hib disease, with only sporadic cases reported after 2009. IPD incidence fluctuated over the study period and has increased in recent years despite high coverage (≥ 90%) of the primary pneumococcal conjugate vaccine (PCV) series since 2019. PCV introduction markedly reduced the frequency of serotypes covered by PCV10. Serotype 3 and non-vaccine serotypes persisted, particularly among adults and infants aged < 1 year. Adults aged ≥ 40 years were predominantly affected by IPD, whereas invasive Hib disease mainly occurred in children aged 1–4 years. None of the patients had been previously vaccinated against IPD or invasive Hib disease. Case-fatality rates were significantly higher for IPD (9.6%) than for Hib disease (3.5%) (p = 0.0361). In the overall population, PCV10 serotypes declined sharply after vaccine introduction (from 55% to 22%), while PCV13-non-PCV10 serotypes remained stable ( 40%), and non-vaccine serotypes increased (from 11% to 28%), with the additional emergence of PCV20-non-PCV15 serotypes. Conclusion. The Hib immunization program achieved sustained disease control in the AP of Vojvodina, while IPD remains a public health concern due to persistent serotype 3 and emerging non-vaccine serotypes. Continued surveillance and consideration of higher-valency pneumococcal vaccine (minimum PCV13) or adult-targeted vaccination strategies are crucial to further reduce disease burden.